Social networks in the global educational space - Diadichenko E. A. (Educational environment today: development strategy, 2018)
The article considers social networks as one of the components of information technologies in the system of the world educational space. Social networks are represented by the mechanism of social interaction, without which social and cultural development is impossible. Network education is a system independent of the formal structures, which functions solely due to the individuality of its participants.
Keywords: информационные технологии; образовательный процесс; социальные сети; информационное пространство; информационно-образовательное пространство; educational process; information technologies; социокультурное развитие; social networks; information and educational space; information space; socio-cultural development